2022
DOI: 10.1371/journal.pgen.1010477
|View full text |Cite
|
Sign up to set email alerts
|

A new mouse model of Charcot-Marie-Tooth 2J neuropathy replicates human axonopathy and suggest alteration in axo-glia communication

Abstract: Myelin is essential for rapid nerve impulse propagation and axon protection. Accordingly, defects in myelination or myelin maintenance lead to secondary axonal damage and subsequent degeneration. Studies utilizing genetic (CNPase-, MAG-, and PLP-null mice) and naturally occurring neuropathy models suggest that myelinating glia also support axons independently from myelin. Myelin protein zero (MPZ or P0), which is expressed only by Schwann cells, is critical for myelin formation and maintenance in the periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…In 2015, Brügger and colleagues 34 showed that P0 expression was fundamental for the maintenance of paranodal/nodal integrity and axonal function through interaction with the neurofascins, and speculated that this mechanism might be impaired by some MPZ mutations related to late-onset axonal neuropathy. These findings were corroborated by Shackleford and coauthors, 35 who generated a p.Thr124Met knock-in mouse model that showed prominent alterations in non-compact myelin domains such as paranodes, Schmidt-Lanterman incisures and gap junctions, implicated in Schwann cell-axon communication and axonal metabolic support. Nevertheless, this hypothesis remains to be confirmed and verified in its specificity for MPZ mutations.…”
Section: Neuromuscularmentioning
confidence: 54%
“…In 2015, Brügger and colleagues 34 showed that P0 expression was fundamental for the maintenance of paranodal/nodal integrity and axonal function through interaction with the neurofascins, and speculated that this mechanism might be impaired by some MPZ mutations related to late-onset axonal neuropathy. These findings were corroborated by Shackleford and coauthors, 35 who generated a p.Thr124Met knock-in mouse model that showed prominent alterations in non-compact myelin domains such as paranodes, Schmidt-Lanterman incisures and gap junctions, implicated in Schwann cell-axon communication and axonal metabolic support. Nevertheless, this hypothesis remains to be confirmed and verified in its specificity for MPZ mutations.…”
Section: Neuromuscularmentioning
confidence: 54%
“…At this point, this remains an observation of unknown causal relation to the MPZ neuropathy; mitochondrial abnormalities are to our knowledge not an established feature of MPZ neuropathy thus far. Nevertheless, mitochondrial alterations were clearly more frequent than generally observed in muscle biopsies and were in line with altered size, function, and distribution of axonal mitochondria in a mouse model of MPZ neuropathy [72]. Furthermore, denervation causes extensive muscle fiber changes including myofibrillar disintegration (target phenomena) and remodeling of the sarcoplasmic reticulum [49], which should also affect muscle fiber mitochondria.…”
Section: Discussionmentioning
confidence: 91%
“…While CMT1‐associated mutations strongly perturbed intercellular adhesions or were retained in the cytoplasm, CMT2‐associated mutations only moderately reduced intercellular adhesions in cultured cells [ 90 ] or mainly affect axo‐glial interactions [ 60 , 72 , 90 , 91 ], including axo‐glial interactions to stabilize nodes and paranodes [ 72 , 92 ]. In line with a loss of function mutation, CMT2 patient #17 with onset in the 3rd decade of life had a novel c.73_74 delinsA (p.S25TfsX22) variant.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ‘CMT2-surface’ surrounds the glycosylation site suggesting this region likely interacts with the glycan in a particular way, perhaps to properly position the lg MPZ domain with respect to the membrane. lndeed, mutations in the consensus N-linked glycosylation site lead (N 122 XT) cause late-onset CMT2 phenotypes in humans and mice (Shackleford et al, 2022; Shy et al, 2004) with morphological changes in the areas of non-compacted myelin. Glycosylation has also been found to alter the adhesion activity of MPZ in heterologous systems, suggesting it helps optimally position MPZ for interaction with other components (Filbin & Tennekoon, 1991, 1993).…”
Section: Discussionmentioning
confidence: 99%